High Q GaN/SiC-Based SAW Resonators for Humidity Sensor Applications - Dan Vasilache; Claudia Nastase; George Boldeiu; Monica Nedelcu; Catalin Parvulescu; Adrian Dinescu; Alexandru Muller (Micromachines)
This paper presents the simulation and experimental results for high-frequency surface acoustic wave (SAW) sensors for humidity detection. The SAW structures with a wavelength of 680 nm are fabricated on GaN/SiC and presented two resonance frequencies: ~6.66 GHz for the Rayleigh propagation mode and ~8 GHz for the Sezawa mode. A SiO2 thin layer (~50 nm thick) was employed for the functionalization of the SAW. Relative humidity characterization was performed in the range of 20–90%. The SAW sensors achieved high values of humidity sensitivity for both adsorption and desorption. The Sezawa mode showed about 2.5 times higher humidity sensitivity than the Rayleigh mode: 17.2 KHz/%RH versus 6.17 KHz/%RH for adsorption and 8.88 KHz/%RH versus 3.79 KHz/%RH for desorption.